Bell’s Palsy: A Review - Sumanta Sourav (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bell’s palsy is a facial nerve defect of unknown etiology. The aim of this article is to put forth a review onBell’s palsy and identifying its clinical presentation, differentiate it from other similar conditions, having abrief idea of various existing treatment modalities. Treatment usually focuses on restoring the function offacial muscles and recovery